Effects of high‐intensity interval walking training on muscle strength, walking ability, and health‐related quality of life in people with diabetes accompanied by lower extremity weakness: A randomized controlled trial - Yasuko Ichihara; Hiroyasu Mori; Motomu Kamada; Tetsuya Matsuura; Koichi Sairyo; Mizusa Hyodo; Rie Tsutsumi; Hiroshi Sakaue; Ken‐ichi Aihara; Makoto Funaki; Akio Kuroda; Munehide Matsuhisa (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction This study examined the effects of high‐intensity interval walking training (IWT) compared to moderate‐intensity continuous walking training (CWT) on muscle strength, walking ability, and health‐related quality of life (QOL) in people with diabetes accompanied by lower extremity weakness. Materials and Methods People with diabetes accompanied by low isometric knee extensor strength using a simple manual dynamometer (n = 50) were screened and randomly divided into 2 groups: CWT (n = 25) and IWT (n = 25). Both groups were instructed by a physical therapist to perform walking training with the goal of 120 min/week over a 5‐month period. The primary outcome, mean change of isometric knee extensor strength, and secondary outcomes, such as gait speed and health‐related QOL, were measured at baseline and the end of the intervention. Results At the end of the intervention, there was no significant difference in the degree of change in isometric knee extension strength between the two groups. However, there was a significant increase in changes in gait speed and physical QOL in the IWT group (gait speed, P < 0.01; physical QOL, P < 0.05). Conclusions The present study showed that IWT for people with diabetes accompanied by lower extremity weakness did not improve knee extension muscle strength compared to CWT but did improve walking ability and physical QOL.